2018
DOI: 10.1051/matecconf/201815401092
|View full text |Cite
|
Sign up to set email alerts
|

Challenge and opportunity research in blood supply chain management: a literature review

Abstract: An interconnected series of the blood management is called blood supply chain management (BSCM). The stages of BSCM consisted of blood collecting, production, inventory, and distribution. The main challenges in BSCM are related to shortage, outdate, and supply chain cost which needed to minimize. Naturally, problems in BSCM are complex, it is not an easy task to find the solution. This complexity brought by several factors as follows: its inflicted risk, the uncertainty of supply and demand, blood nature as pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The study identified 227,944 RBC transfusions for 40 At the participating hospital blood banks, the mean (SD) of daily RBC demand was 92.43 (28.27) units. The mean (SD) of the daily ordering quantity was 103.71 (69.49) units, which was significantly higher than the actual daily demand (difference in means: 11.27; 95% CI: 9.09, 13.46; p-value <0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study identified 227,944 RBC transfusions for 40 At the participating hospital blood banks, the mean (SD) of daily RBC demand was 92.43 (28.27) units. The mean (SD) of the daily ordering quantity was 103.71 (69.49) units, which was significantly higher than the actual daily demand (difference in means: 11.27; 95% CI: 9.09, 13.46; p-value <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…A significant cost saving was achieved, mainly through leaner inventory, contrasting with actual hospital blood bank inventory levels that are excessive, highly variable, and associated with an increasing trend over time. 26 Although there have been many studies in the field of blood demand and supply management, [40][41][42][43][44] these typically assume independent and identically distributed demands, which is rarely the case, as the demand of blood has temporal dependence and is affected by clinical indicators. To our knowledge, our study team was the first to consider integrating demand forecasting models into blood inventory management strategies using electronic medical records.…”
Section: Notementioning
confidence: 99%
“…Recent literature reviews on blood supply chains can be found in (Pirabán et al, 2019), (Mansur et al, 2018), (Osorio et al, 2015) and (Beliën and Forcé, 2012). And a substantial number of articles study inventory management of blood components and perishable commodities.…”
Section: Related Workmentioning
confidence: 99%
“…Blood transfusion is an excellent example of complex health care process 2,3 being constituted by a set of interdependent sub‐processes involving different professionals where any error happening at any stage may cause serious consequences on the downstream phases and ultimately on patients 4,5 . The most common errors encompass patient misidentification, incorrect sample collection and labelling, incomplete or incorrect data entry, prescription and transcription errors, laboratory errors, inappropriate management of storage devices, inappropriate order of blood products, inaccurate handling, delivery and administration 6,7 .…”
Section: Introductionmentioning
confidence: 99%